Corrigendum (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Minor changes are required in the Funding information and the acknowledgement for the article entitled “Organosulphur Compounds Induce Apoptosis and Cell Cycle Arrest in Cervical Cancer Cells via Downregulation of HPV E6 and E7 Oncogenes” in “Anti-Cancer Agents in Medicinal Chemistry, 2021, Vol. 21, No. 3, pp. 393-405.” The correct Funding information and Acknowledgement is given below: FUNDING: This project was funded by the Council of Science and Technology (CST), Lucknow, Uttar Pradesh, India (Sanction No. CST/374). The financial support during this research was also provided by the Deanship of Scientific Research, King Khalid University, Abha, Saudia Arabia through the General Research Project under grant number R.G.P. 01/48/42. ACKNOWLEDGEMENT: IAA is greatly thankful to the Council of Science and Technology (CST), Uttar Pradesh, India, for providing him project as a Principal Investigator. Authors would also like to acknowledge the support of the King Khalid University through the General Research Project under grant number R.G.P. 01/48/42. under the Deanship of Scientific Research, King Khalid University, Abha, Saudia Arabia